Robotic Fabrication in Architecture, Art and Design 2018 2018
DOI: 10.1007/978-3-319-92294-2_26
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Robotic Carving

Abstract: The paper presents the developments of a series of methods to train a fabrication system for the integration of material performances in timber manufacturing processes, combining robotic fabrication together with different sensing strategies and machine learning techniques, and their further application within a prototypical design to manufacturing workflow. The training cycle, spanning from the recording of skilled human experts to autonomous robotic explorations, aims to encapsulate different layers of instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, when combined with robotic assembly, the use of the robot overcomes the need to reposition and reprocess the working piece, which may also decrease tolerances and allow for more design possibilities (20). Applications of subtractive robotic processes range from cutting and sawing (21)(22)(23)(24), milling (25)(26)(27), and drilling (20) to carving (28). Besides additive and subtractive processes, we can also delimit deformative processes, such as wire bending (29,30), metal sheet bending or folding (31,32), and incremental sheet forming (33).…”
Section: Construction Automationmentioning
confidence: 99%
“…However, when combined with robotic assembly, the use of the robot overcomes the need to reposition and reprocess the working piece, which may also decrease tolerances and allow for more design possibilities (20). Applications of subtractive robotic processes range from cutting and sawing (21)(22)(23)(24), milling (25)(26)(27), and drilling (20) to carving (28). Besides additive and subtractive processes, we can also delimit deformative processes, such as wire bending (29,30), metal sheet bending or folding (31,32), and incremental sheet forming (33).…”
Section: Construction Automationmentioning
confidence: 99%
“…In addition, researchers have successfully showcased the viability of augmented robotic manufacturing systems by employing diverse methods and materials. These include additive production processes with cementitious (Çapunaman et al, 2022;Ercan Jenny et al, 2020;Im et al, 2018;Naboni, 2022) and thermoplastic materials (Felbrich et al, 2022;Kwon et al, 2019;Nicholas et al, 2020), subtractive production processes involving carving and milling techniques (Brugnaro & Hanna, 2019;Çapunaman et al, 2022;Garcia del Castillo y Lopez, 2022;Shaked et al, 2021), and formative production processes utilizing various material systems (Mueller et al, 2019;Rossi & Nicholas, 2018).…”
Section: Augmented Fabricationmentioning
confidence: 99%
“…Recent research has demonstrated the application of adaptive robotic subtractive manufacturing processes for stone carving [19] and wood [20], where the visualization and predictive techniques afforded by adaptive processes enable human-like responsiveness towards working with the material. Adaptive processes have also been utilized for the localization and calibration of a mobile robotic fabrication system for building-scale mesh welding [21], increasing accuracy through continuous mapping of the environment and surveying of the fabrication process.…”
Section: Related Workmentioning
confidence: 99%